Personality, Gender, and Age as Predictors of Media Richness Preference - David R. Dunaetz; Timothy C. Lisk; Matthew Minsuk Shin (Advances in Multimedia)
Media richness, the degree to which a specific media transmits information in multiple channels, is an important concept as the number of available multimedia communication methods increases regularly. Individuals differ in their preferences for media richness which may influence their choice of communication multimedia in a given situation. These preferences can influence how successful their communication efforts will be. This exploratory study of 299 adults (ages 16–84) with at least a basic ability to compute examines the relationship between multimedia preference and age, gender, and personality traits. Males and people with higher levels of extraversion and agreeableness were found to have a higher preference for media richness. Age was not a significant predictor of media richness preference.